A CASE REPORT: A SCROTAL FLAP FOR PENILE PARAFFINOMA RECONSTRUCTION - Rr. Theodora Ratih Labdagati Iswara; Muhammad Aulia Ul Hakim; Jahnavi Malineni; Katrina Ysabelle Hidalgo (Jurnal Rekonstruksi dan Estetik)
Highlights: